2005
DOI: 10.1590/s0103-50532005000400016
|View full text |Cite
|
Sign up to set email alerts
|

Selective catalytic reduction of NO to N2 with copper and cobalt exchanged ZSM-5 zeolites: the effect of calcium addition

Abstract: Zeólitas ZSM-5 contendo cobre ou cobalto, ou simultaneamente cobre e cálcio, ou cobalto e cálcio foram preparadas por troca-iônica e testadas como catalisadores na redução de NO a N 2 na presença de metano ou propano. . Nestes catalisadores a presença de cálcio não provocou diferenças significativas na atividade específica para a redução de NO ou para a oxidação do metano.ZSM-5 catalysts containing either Cu or Co cations individually or Cu/Ca or Co/Ca cation combinations were prepared by ion exchange. These m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In the promoted sorbent Cu 0.10 Zn 0.90 O/SiO 2 , the intensity of this absorption band is higher than that in the sorbent Cu 0.01 Zn 0.99 O/SiO 2 . The similar absorption band was reported in the UV–vis DRS spectra of the Cu‐containing zeolites at 600–850 nm . This absorption band was attributed to the Cu 2+ cations in octahedral coordination environment.…”
Section: Resultssupporting
confidence: 81%
“…In the promoted sorbent Cu 0.10 Zn 0.90 O/SiO 2 , the intensity of this absorption band is higher than that in the sorbent Cu 0.01 Zn 0.99 O/SiO 2 . The similar absorption band was reported in the UV–vis DRS spectra of the Cu‐containing zeolites at 600–850 nm . This absorption band was attributed to the Cu 2+ cations in octahedral coordination environment.…”
Section: Resultssupporting
confidence: 81%
“…The first band, at wavelengths around 270 nm, is assigned to oxygento-metal charge transfer related to Cu(I) or Cu(II) species stabilized in the zeolite framework. [30][31][32] The origin of the broad band at wavelengths above 550 nm has been interpreted differently in the open literature. [32][33][34][35] On the one hand, Bennici et al 33 suggested that the position of the absorption maximum of this band is dependent on the nuclearity of CuO x clusters, i.e.…”
Section: Structure Composition and Acidity Of The Me-ssz-13 Zeolitesmentioning
confidence: 99%
“…[30][31][32] The origin of the broad band at wavelengths above 550 nm has been interpreted differently in the open literature. [32][33][34][35] On the one hand, Bennici et al 33 suggested that the position of the absorption maximum of this band is dependent on the nuclearity of CuO x clusters, i.e. the lower the wavelength of the absorption, the larger the clusters and vice versa.…”
Section: Structure Composition and Acidity Of The Me-ssz-13 Zeolitesmentioning
confidence: 99%
“…For the |Na|[Si 12 Al]-MFI and |Na|[Si 25 Al]-MFI zeolites an additional signal at 0 ppm is observed, which increases corresponding to peak 2 (A2) does not correspond to the total hydrogen consumption (H 2 /Me total). This difference in the H 2 consumption might be attributed to the presence of CuO, whose content in each catalyst (show in Table 5 CuO can be formed during calcination from hydroxylated species generated during the ion exchange 19 , such as Cu n+ (OH) n , Cu (n+m)+ (OH) m (O-CO-CH 3 ) n or Cu n+ (OH) m (n-m)+ , resulting in a pH decrease from 5.5 to 4.9.…”
Section: Catalyst Characterisationmentioning
confidence: 99%